Biomarker responses of the estuarine brown shrimp Crangon crangon L. to non-toxic stressors: Temperature, salinity and handling stress effects - Menezes, Salomé
Biochemical biomarkers in common estuarine species, such as the brown shrimp Crangon crangon, have the potential to provide early warning of contaminant exposure from field collected samples and through the development of in situ tests. The biomarkers acetylcholinesterase (AChE), lactate dehydrogenase (LDH) and glutathione S-transferase (GST) have been shown to provide evidence of exposure to contaminants in a number of species and field situations. As they may naturally respond to the marked physicochemical changes found in estuaries (thus confounding contaminant-induced effects), this work aims to determine the effects of salinity, temperature and handling stressors on these biomarkers in C crangon. AChE recovery in field-collected shrimp transplanted to clean laboratory conditions suggests the presence of inhibiting factors at the sampling site (River Minho estuary). Maintenance time in stock tanks had effects that led to the choice of a minimum 15-day maintenance period of C. crangon in the laboratory before subsequent use of the enzymes as effect criterions in toxicity assays. Field levels of biomarker activity were unaffected following field-laboratory transportation of C. crangon, making this factor unlikely to jeopardize detection of contaminant associated effects. LDH levels were significantly lower under conditions that mimic a diumal salinity fluctuation, increasing under low salinity conditions; this potentially indicates increased energy costs associated with raised osmoregulatory demands. It is recommended that a lower limit to field exposure of in situ tests should be based on salinity. Higher temperatures led to higher AChE activities and this is in agreement with the existing evidence of increases of endogenous AChE levels as a function of temperature (within a certain range). To avoid misinterpretation of biomarker responses, studies such as this are an important contribution to the establishment of reference activity levels against which biomarker changes can be estimated and are therefore essential preliminary steps in the development of in situ bioassays using biomarkers. (c) 2006 Elsevier B.V. All rights reserved.